The guide in determining the criteria in developing contract parameters of shari’ah compliant e-commerce / Roshaimizam Suhaimi, Muhamad Rahimi Osman and Ismail Ahmad - Suhaimi, Roshaimizam; Osman, Muhamad Rahimi; Ahmad, Ismail (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
E-commerce has become a common phenomenon today throughout the world, including Malaysia. Muslims, too, have been involved in this modern activity in order to fulfill their obligatory needs and individual necessities. Therefore, it is very important to ensure all e-commerce related activities conform to the basic principles of selling and buying according to the current fiqh muamalat and viewpoint of scholars in relation to the contract. Using the qualitative method approach, this article aims to underline some criteria to be used as a guide in developing the parameters of e-commerce contracts which are shari’ah compliant. The researcher uses the literature review and interview for data collection in identifying and determining the relevant criteria of guide in developing e-commerce parameters. In determining the main dimension, it must be verified through the method of interview with informant of muamalat experts. Results of the study found that e- ommerce parameters comprise of three main dimensions and twenty-eight guide items to ensure that e-commerce contracts are shari’ah compliant.